From the workers' adult education to the trade union higher education system in France: The Regional Employment Institutes - Regina Maria Caruccio Martins (Arizona State University, 2011)
This presentation on the hystorical context of the trade union adult education, limits itself to the 20th century, beginning with the postwar years till the creation of the first Regional Instituto of Employment, in 1956. The socio-economic conditions, as well as the policies of the time, determined the development of the workers social right that eventually led to the right to training and education. My role as a research professor at the IRT (2006- 2007) enabled me to enjoy the productions and discussions held by the institutes experts in several fields (economists, lawyers, sociologists and historians) to carry out my research work on the unionism in France. In my capacity as an expert in adult education, I aimed to demonstrate through the data I could gather, the role that lifelong education plays in the education of the trade union workers, regardless of the ideologycal orientation the union may have, as it concerns a right embedded in the Civil Code which every worker is entitled to.